2021
DOI: 10.1039/d1ob01275d
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous conversion of prenyl halides to acids: application in metal-free preparation of deuterated compounds under mild conditions

Abstract: Here we reveal a simple generation of deuterium halide (DX) from common and inexpensive reagents readily available in a synthetic chemistry laboratory, i.e. prenyl-, allyl-, and propagyl halides, under mild...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…16 Under acid/base-mediated conditions, selective deuterium-incorporation at C3 is controlled by the molecule's intrinsic reactivity (4). [17][18][19][20] Similar reactivity has been achieved using organocatalysts, 21 Ru3(CO)12, 22 or AgOTf. 23 Selective deuteration at C2 can currently only be achieved using directed approaches (5): ortho-lithiation 17 or transition-metal catalyzed methods requiring a directing group on the indole nitrogen.…”
mentioning
confidence: 66%
“…16 Under acid/base-mediated conditions, selective deuterium-incorporation at C3 is controlled by the molecule's intrinsic reactivity (4). [17][18][19][20] Similar reactivity has been achieved using organocatalysts, 21 Ru3(CO)12, 22 or AgOTf. 23 Selective deuteration at C2 can currently only be achieved using directed approaches (5): ortho-lithiation 17 or transition-metal catalyzed methods requiring a directing group on the indole nitrogen.…”
mentioning
confidence: 66%
“…The synthesis of a deuterated version of 29 was first reported in 1997 by Best et al, although the exact positions of H/D exchange were not given . More recently, Darshana et al reported the H/D exchange of dexamethasone at C-6 based on the in situ spontaneous generation of deuterium chloride (DCl) from a prenyl chloride ( 32 ) under mild conditions (rt, 48 h) in CD 3 OD (Scheme a) . The generated DCl induced H/D exchange within the dexamethasone at the α and γ positions next to the carbonyl groups of 29 via acid catalysis chemistry, resulting in 74% deuterium incorporation in 33 , produced in 98% yield (Scheme b).…”
Section: Deuterated Drugs As Therapeutics For the Treatment Of Covid-19mentioning
confidence: 99%
“…First, Habler et al developed and validated a two-dimensional isotope-dilution liquid chromatography tandem mass spectrometry (ID-LC-MS/MS) method for the accurate and simultaneous quantification of drugs in human serum, specifically for quantifying several repurposed COVID-19 drugs simultaneously. 70 The work was performed using stable deuterium-labeled analogues chloroquine-d 4 phosphate (47), hydroxychloroquine-d 4 sulfate (48), ritonavir-d 6 (49), lopinavir-d 8 (50), and azithromycin-13 C-d 3 (51) as internal MS standards (Figure 7), all commercially sourced. The dosage of repurposed COVID-19 therapeutics is typically derived from in vitro-generated half-maximum effective concentration (EC 50 ) values for SARS-CoV-2 and pharmacology-based pharmacokinetic models from other diseases and clinical conditions.…”
Section: Standardsmentioning
confidence: 99%
“…We hypothesized that, instead of the previous oxidative pathway mediated by stoichiometric Cu­(II), a redox-neutral hydrodeacylation could be realized with catalytic copper by utilizing the N–H hydrogen of a PAI as the H-atom source to quench the R2 radical (Scheme C). Considering that the relatively acidic ketone α-hydrogens and the N–H hydrogens of PAIs can be easily deuterated at different stages via H/D exchange with D 2 O, various degrees of deuteration could be achieved, in principle, via different combinations of operations from the same ketone precursor. For example, if only the N–H hydrogen of a PAI is deuterated, a monodeuteration process is anticipated.…”
mentioning
confidence: 99%
“…As a result, this protocol (condition a) generally gave high overall monodeuteration for a range of substrates (Table ) along with high isotope purity observed from the 13 C NMR and HRMS (see Supporting Information). To realize dideuteration, α-deuteration of the ketone substrates was first carried out via H/D exchange with D 2 O using pyrrolidine as the catalyst, and then, the key was to avoid deuterium loss during the PAI formation. The optimal conditions (condition b) were found to use fully deuterated MPHA (prepared via H/D exchange of MPHA with D 2 O) to condense with the α-deuterated ketone; the resulting PAI can easily lose the D on the nitrogen via H/D exchange with H 2 O in the C–C cleavage step.…”
mentioning
confidence: 99%